Answer:
Step-by-step explanation:
We know that if a figure is reflected across y axis then its y coordinate remains same but the x coordinate changes its polarity.
i.e. the function will become .
Now, the given function :
Then , after reflection across y axis the new function will become:
Answer:
(-(7-9))(z)-6z= 8(-6+2)
Simplify
-(-2)(z) -6z =8(-6+2)
Multiply 8*-6 and 8*2
2z -6z= -48+16
Combine like terms
2z+-6z =-32
-4z=-32
Divide both sides by -4
z=8
Step-by-step explanation:
IdentityProperty of Addition OR Zero Property
In this case, we'll have to carry out several steps to find the solution.
Step 01:
Data
f(x) = √3x
g(x) = √48x
(f . g)(x) = ?
Step 02:
(f . g)(x) :
(f.g)(x) = 12 √ x
The answer is:
(f.g)(x) = 12 √ x